2013
DOI: 10.1158/0008-5472.can-12-3165
|View full text |Cite
|
Sign up to set email alerts
|

Histone Demethylase RBP2 Promotes Lung Tumorigenesis and Cancer Metastasis

Abstract: The retinoblastoma binding protein RBP2 (KDM5A) is a histone demethylase that promotes gastric cancer cell growth and is enriched in drug-resistant lung cancer cells. In tumor-prone mice lacking the tumor suppressor gene RB or MEN1, genetic ablation of RBP2 can suppress tumor initiation, but the pathogenic breadth and mechanistic aspects of this effect relative to human tumors have not been defined. Here, we approached this question in the context of lung cancer. RBP2 was overexpressed in human lung cancer tis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
136
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(142 citation statements)
references
References 46 publications
5
136
1
Order By: Relevance
“…or suppressing the expression of cyclin-dependent kinase inhibitor (CDKIs) p21(CIP1), p27(kip1) etc. by altering H3K4 methylation at the promoters of target genes [40, 41]. Here, we provide evidence that RBP2 decreased the expression of miR-21 epigenetically.…”
Section: Discussionmentioning
confidence: 78%
“…or suppressing the expression of cyclin-dependent kinase inhibitor (CDKIs) p21(CIP1), p27(kip1) etc. by altering H3K4 methylation at the promoters of target genes [40, 41]. Here, we provide evidence that RBP2 decreased the expression of miR-21 epigenetically.…”
Section: Discussionmentioning
confidence: 78%
“…This molecule should be associated with cell cycle since tumorigenesis is closely related with uncontrolled cell proliferation. Published data showed that Cyclin D1 was a downstream target of RBP2 in lung cancer [23], so we tried to testify this in GC. As can be seen in Figure 5A and 5B, when RBP2 was inhibited in BGC-823 cells, Cyclin D1 expression decreased both at mRNA and protein level, which was in line with the finding in lung cancer.…”
Section: Resultsmentioning
confidence: 99%
“…The KDM5 Cluster (JARID1 Subfamily) KDM5A (JARID1A) promotes gastric cancer cell growth and is enriched in drug-resistant lung cancer cells. The depletion of this protein from lung cancer tissues, indeed, drastically affects cell proliferation, motility, migration, invasion, and metastasis [132] In this context, KDM5A binds to integrin-b1 (ITGB1) promoters and induces its expression. Integrin-b1, in turn, plays key roles in lung cancer metastasis.…”
Section: The Kdm4 Cluster (Jmjd2 Subfamily)mentioning
confidence: 99%
“…Integrin-b1, in turn, plays key roles in lung cancer metastasis. Simultaneously, KDM5A induces the expression of cyclins D1 and E1 while suppressing the expression of cyclin-dependent kinase inhibitor p27 (CDKN1B), each contributing to KDM5A-mediated cell proliferation [132,133]. Besides its roles in gastric and lung cancer, KDM5A has been suggested to contribute, through its interaction with retinoblastoma protein (pRb), to uncontrolled growth in malignant melanomas.…”
Section: The Kdm4 Cluster (Jmjd2 Subfamily)mentioning
confidence: 99%